THE MADINAH CHARTER IN NOTES: TOLERANCE BETWEEN RELIGIOUS PEOPLES FROM THE PERSPECTIVE OF THE PROPHET'S HADITH - Adhi Irawan Sastramiharja (STAI Sebelas April Sumedang, 2024)
In several respects, Islam is often referred to as a discriminatory religion, especially in relation to relations between religious communities. This accusation is based on the many hadiths which editorially show this attitude. In fact, the Prophet Muhammad as the speaker and every word he said became a role model and legal basis for Muslims has provided an example of how tolerance should be exercised with other religions. The Medina Charter was a form of legal protection given to the very diverse people of Medina at that time. Historians view the Medina Charter as an authentic text created by Islamic civilization and its authenticity is beyond doubt. The important content of the Medina charter is an effort to form a harmonious system, regulate the people and uphold a system of government based on basic equality of rights. This article elaborates on the typology of hadiths regarding religious relations, the socio-historical context behind their emergence and a constructive reading model for the current context and to prove that the values ​​contained in the articles contained in the Medina Charter actually contain religious principles and state, such as peace, protection and equal rights. The method used in this research is a qualitative method with a literature study approach. The results of this research show that human values ​​are contained in Articles 1, 23, and 42. Articles 3 and 11, 20, 47 contain. regarding individual rights, Articles 25 and 33 regarding freedom. Keywords: Tolerance; hadith; Medina Charter.